ANALISIS PERBANDINGAN HARGA POKOK PRODUKSI DENGAN MENGGUNAKAN METODE FULL COSTING DAN ACTIVITY BASED COSTING (ABC) GUNA PENENTUAN HARGA JUAL TELUR PUYUH - Ismi Febriani; Herlina Pusparini; Isnawati Isnawati; Tri Hanani (Proceeding Maritime Business Management Conference, 2024)
This study aimed to compare the cost of commodities produced through the use of activity-based costing versus full costing techniques. One of the micro, small, and medium-sized businesses involved in organic quail egg farming is Organik Quail Farm. Organik Quail Farm has never used the whole costing approach, often known as ABC, to determine the cost of commodities produced since its founding. This study, which compares an explanatory study with a comparison study, is descriptive quantitative research. Three methods are utilized to acquire data: documentation, interviews, and observation. The study's findings show that employing the ABC technique of calculation resultsed in greater production costs than complete costing method calculation. Production costs using the complete costing technique come to Rp. 26,940,908. With 1260 trays produced in a single production utilizing the complete costing approach, the production cost is Rp. 26,940,908; this works out to Rp. 21,328 per tray. In contrast, the activity-based costing method yields production costs of Rp. 26.409.281 for a single production cycle that produces 1260 trays; this method's cost of production is Rp. 20,960 per tray. The cost of items produced per tray employing this method is Rp 20,960. One manufacturing cycle produces 1260 trays. The results obtained using the comprehensive costing approach are Rp 422 larger than those obtained with the activity-based costing method, which is 0.019% smaller.